Blade breaker - Aveyard, Victoria (Aveyard, Victoria. Realm breaker series., 2022)
"Dom, a grieving immortal, strives to fulfill a broken oath. Sorasa, an outcast assassin, faces her past when it returns with sharpened teeth. Valtik, an old sorceress, summons a mighty power. And Corayne, a pirate's daughter with an ancient magic in her blood, steps closer to becoming the hero she's destined to be. Together they must assemble an army to face Queen Erida and Taristan's wicked forces. But something deadly waits in the shadows, something that might consume the world before there's any hope for victory"--